PREVALENCE OF PSYCHOACTIVE SUBSTANCE USE AMONG STUDENTS OF SECONDARY MEDICAL SCHOOL “THE SISTERS OF MERCY” IN MOSTAR (Zdravstveni glasnik, 2024)
INTRODUCTION: The onset of tobacco, alcohol and psychoactive substance use is usually associated with adolescence. Young people are the age group most at risk of adopting and developing addictive behavior due to specificity of the formative years, relative inexperience and risk appetite. OBJECTIVE: The objective of this study is to investigate the use of psychoactive substances in secondary school students in Mostar, and compare the results of prevalence of psychoactive substance use among students of secondary medical school and secondary school for economics. SUBJECTS AND METHODS: The study was conducted from October 1 through December 31, 2018. A total of 97 students from the secondary medical school and 96 students from the secondary school for economics were surveyed. The ESPAD questionnaire was used as the research instrument. RESULTS: The most common types of risk behaviors among students from both schools were smoking and consumption of alcoholic beverages. Students with poor academic performance come into contact with cigarette smoking significantly earlier and misuse glue and other solvents significantly more than students with good academic performance (p